The effectiveness of prophylactic antibiotics and betadine skin preparation on cranial cutaneous Cutibacterium acnes – A prospective study. (June 2022) - Nowicki, Jake; Mills, Michael; Van Der Veken, Jorn; Pantelis, Ioanna; Daniels, Santhosh; Poonnoose, Santosh
Highlights: Cutibacterium acnes is a common cause of cranial wound infections. Prophylatic antibiotics and surgical skin preparation are effective at eradicating Cutibacterium acnes from the skin surface but not from the underlying dermis. Cutibacterium acnes in the untreated dermis may be a target for reducing Cutibacterium acnes cranial wound infections. Abstract: Background: Cutibacterium acnes, formerly known as Propionibacterium acnes, is increasingly recognized as a cause of surgical site infection and implant failure despite the use of prophylactic antibiotics and antiseptic surgical preparations. The aim of this study was to investigate whether C. acnes persists in the dermal layer of the skin after standard perioperative antibiotics and skin prepping with alcoholic betadine solution in consecutive patients undergoing a craniotomy. Methods: A single centre prospective observational study was performed at Flinders Medical Centre. Adult patients undergoing a cranial neurosurgical intervention between October 2019 to March 2021 were eligible for inclusion. After administration of standard preoperative antibiotics (Cefazolin), three swabs were taken for each patient: one before prepping the skin with alcoholic betadine, one after prepping the skin and a dermal swab once the skin was incised. Results: 73 patients were included. Cutibacterium acnes cultures were positive in 61 patients of the "pre-prep" group (83.6%), 12 (16.4%) in the "post-prep" group, and 53 (72.6%) were from dermal swabs There was a significant reduction of positive cultures of the skin after surgical preparation was applied (p < 0.00001). There was a non-significant reduction of positive cultures in the dermal swabs after skin preparation (p = 0.068) Conclusions: Cutibacterium acnes persists within the dermis of the scalp despite standard prophylactic measures using alcoholic betadine solution and cefazolin.